Clinical Applicability of Monitoring Antihypertensive Drug Levels in Blood. Issue 1 (July 2020) - Peeters, Laura E.J.; Feyz, Lida; Boersma, Eric; Daemen, Joost; van Gelder, Teun; Koch, Birgit C.P.; Versmissen, Jorie
Abstract : Dried blood spot (DBS) analysis is a novel analytical method for therapeutic drug monitoring to identify nonadherence to antihypertensive drugs. This study was conducted to evaluate the clinical applicability of measuring drug concentrations of 8 antihypertensive drugs, using DBS and venipuncture. Furthermore, this study aimed to provide more insight into the between-patient variability in drug concentrations. False-negative values from DBS compared with a venipuncture were determined to assess drug adherence. A generalized estimating equation was used to estimate the model parameters, including sex, dose, age, weight, and the time interval, between drug intake and sampling, on the Cplasma (drug concentration in plasma). No false-negative values were found when measuring nonadherence using DBS compared with venipuncture. A high variability in Cplasma between patients was observed, especially at peak concentrations with a fold change reaching from 2.3 to 35.2. The time of intake was significantly related to the height of the Cplasma in 7 of the 8 measured drugs with a P <0.05, but the influence of dose, weight, age, and sex on drug levels differed largely between the measured drugs. DBS is a reliable and convenient method to assess nonadherence to antihypertensive drugs in clinical practice. The Cplasma of the 8 antihypertensive drugs in this study show a large interindividual difference, and therefore, low plasma concentrations do not necessarily mean nonadherence. Nonadherence can only be confirmed if drug levels are undetectable, that is, values below the lower limit of detection. Abstract : Supplemental Digital Content is available in the text.